Cardiomyocyte intracellular cholesteryl ester accumulation promotes tropoelastin physical alteration and degradation: Role of LRP1 and cathepsin S - Samouillan, Valerie; Revuelta-López, Elena; Dandurand, Jany; Nasarre, Laura; Badimon, Lina; Lacabanne, Colette; Llorente-Cortés, Vicenta (The international journal of biochemistry & cell biology, 2014)
Dyslipemia has a direct impact on cardiac remodeling by altering extracellular matrix (ECM) components. One of the main ECM components is elastin, a proteic three-dimensional network that can be efficiently degraded by cysteine proteases or cathepsins. Dyslipemic status in insulin resistance and combined hyperlipoproteinemia diseases include raised levels of very low density lipoproteins (VLDL), triglyceride (TG)-cholesteryl ester (CE)-rich lipoproteins. Enhanced VLDL concentration promotes cardiomyocyte intracellular cholesteryl ester (CE) accumulation in a LRP1-dependent manner. The aim of this work was to analyze the effect of cardiomyocyte intracellular CE accumulation on tropoelastin (TE) characteristics and to investigate the role of LRP1 and cathepsin S (CatS) on these effects. Molecular studies showed that LRP1 deficiency impaired CE selective uptake and accumulation from TG-CE-rich lipoproteins (VLDL+IDL) and CE-rich lipoproteins (aggregated LDL, agLDL). Biochemical and confocal microscopic studies showed that LRP1-mediated intracellular CE accumulation increased CatS mature protein levels and induced an altered intracellular TE globule structure. Biophysical studies evidenced that LRP1-mediated intracellular CE accumulation caused a significant drop of Tg2 glass transition temperature of cardiomyocyte secreted TE. Moreover, CatS deficiency prevented the alterations in TE intracellular globule structure and on TE glass transition temperature. These results demonstrate that LRP1-mediated cardiomyocyte intracellular CE accumulation alters the structural and physical characteristics of secreted TE through an increase in CatS mature protein levels. Therefore, the modulation of LRP1-mediated intracellular CE accumulation in cardiomyocytes could impact pathological ventricular remodeling associated with insulin-resistance and combined hyperlipoproteinemia, pathologies characterized by enhanced concentrations of TG-CE-rich lipoproteins.